Safety and efficacy of a feed additive consisting of butylated hydroxytoluene (BHT) for all animal species (Katyon Technologies Limited) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2022)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of butylated hydroxytoluene (BHT) as a feed additive for all animal species. The additive BHT is considered safe for chickens for fattening and weaned piglets at the maximum proposed concentration of 150 mg/kg complete feed. This conclusion is extended to chickens reared for laying and extrapolated to pigs for fattening. In the absence of data, no conclusion on the safety for the other target species could be drawn. The exposure of the consumer to BHT from tissues and products of animals fed the additive ranged from 1% to 3% of the acceptable daily intake (ADI). The FEEDAP Panel concluded that the use of BHT as a feed additive at the proposed conditions of use is of no concern for the safety of the consumers. Exposure of the user to BHT via inhalation is likely; however, the Panel is not in the position to conclude on the potential inhalation toxicity of the additive. BHT is a skin and eye irritant, no conclusions can be drawn on the potential of the additive to be a skin sensitiser. In the absence of data, the FEEDAP Panel cannot conclude on the safety of BHT for the environment. The additive BHT is considered an efficacious antioxidant in feedingstuffs for all animal species.